Intestinal Epithelial Cells Regulate Gut Eotaxin Responses and Severity of Allergy - Kim, Eunsoo; Lembert, Melanie; Fallata, Ghaith M.; Rowe, John C.; Martin, Tara L.; Satoskar, Abhay R.; Reo, Nicholas V.; Paliy, Oleg; Cormet-Boyaka, Estelle; Boyaka, Prosper N. (Frontiers in Immunology, 2018)
Intestinal epithelial cells (IECs) are known to regulate allergic sensitization. We addressed the role of the intrinsic IKKβ signaling in IECs in the effector phase of allergy following oral allergen challenge and its impact on the severity of symptoms is poorly. Upon orally sensitization by co-administration of ovalbumin with cholera toxin as adjuvant, wild-type and mice lacking IKKβ in IECs (IKKβΔIEC mice) developed similar levels of serum IgE and allergen-specific secretory IgA. However, subsequent allergen challenges in the gut promoted reduced allergic responses in KKβΔIEC mice. Analysis of cytokines and chemokines in serum and gut tissues after oral allergen-challenge revealed impaired CCL11 responses in IKKβΔIEC mice, which correlated with lower frequencies of eosinophils in the gut lamina propria. We also determined that IECs were a major source of CCL11 and that impaired CCL11 production was due to the lack of IKKβ signaling in IECs. Oral administration of CCL11 to IKKβΔIEC mice during oral allergen challenge enhanced allergic responses to levels in wild-type mice, confirming the role of IEC-derived CCL11 as regulator of the effector phase of allergy following allergen challenge. Our results identified targeting IEC-derived CCL11 as potential strategy to limit the severity of allergic responses to food antigens.